2003
DOI: 10.1186/1471-2288-3-12
|View full text |Cite
|
Sign up to set email alerts
|

More insight into the fate of biomedical meeting abstracts: a systematic review

Abstract: BackgroundIt has been estimated that about 45% of abstracts that are accepted for presentation at biomedical meetings will subsequently be published in full. The acceptance of abstracts at meetings and their fate after initial rejection are less well understood. We set out to estimate the proportion of abstracts submitted to meetings that are eventually published as full reports, and to explore factors that are associated with meeting acceptance and successful publication.MethodsStudies analysing acceptance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
100
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(113 citation statements)
references
References 67 publications
8
100
1
4
Order By: Relevance
“…The majority of the previous studies explored the quality of the research project in determining the enablers or disablers of publication of abstracts in peer-reviewed journals. 29,31 Our results, similar to those published from various subspecialties, indicate that more than half of the trainees' research efforts were presented as abstract form only and did not progress to full manuscript. Most research activities performed by responder trainees were retrospective clinical studies, which are a time-efficient and easy way of answering new questions with existing data but still have a higher tendency for non-publication.…”
Section: Discussionsupporting
confidence: 78%
“…The majority of the previous studies explored the quality of the research project in determining the enablers or disablers of publication of abstracts in peer-reviewed journals. 29,31 Our results, similar to those published from various subspecialties, indicate that more than half of the trainees' research efforts were presented as abstract form only and did not progress to full manuscript. Most research activities performed by responder trainees were retrospective clinical studies, which are a time-efficient and easy way of answering new questions with existing data but still have a higher tendency for non-publication.…”
Section: Discussionsupporting
confidence: 78%
“…This rate is comparable with that of other medical The outcome of abstracts presented at the USCAP J Song et al societies with published reports, which typically range from 30 to 50%. [1][2][3][4][5][6] The variation in reported rates may be partly due to different follow-up times, because some studies included publications as far as 5 years after abstract presentation. In a large-scale study, von Elm et al 1 analyzed 19 123 abstracts presented in 234 biomedical meetings from 1957 to 1998, and found the overall publication rates after 1, 2, 3, 4, and 6 years to be 12, 27, 37, 41, and 44% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that abstracts from smaller meetings, US-held meetings, and those involving basic science, with positive outcomes, or presented orally were more likely to be published. 1 Similar studies specific for pathology meetings are very rare. Ciesla and Wojcik 2 analyzed cytopathology abstracts presented in 1998 and found a 33% publication rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately (or perhaps unfortunately), my seemingly private struggle is actually quite common. There are studies that demonstrate that up to one third of abstracts presented at biomedical meeting are never published as complete articles in peer-reviewed journals [2][3][4]. One study found that some reasons for failure to publish ranged from lack of time to prepare a manuscript (most common reason cited) to lack of participation from co-authors to feelings that the responsibility of writing the manuscript belonged to another co-author [3].…”
mentioning
confidence: 99%